GC-MS ANALYSIS OF CONSTITUENTS OF ESSENTIAL OIL FROM LEAVES OF EPHEDRA EGUISETINA BUNGE (Scientific journal of the Fergana State University, 2023)
The article deals with the chemical study of the composition of the essential oil of the plant Ephedra eguisetina Bunge. The essential oil contains 36 compounds and the main compounds are 2-methylnone-2-en-1-ol (15.30%), 2,6-bis (bromomethyl) -1,4-benzene dicarbonitrile (12.90%), phytol (11.47%), glycerildiacetate (8.42%), 6,10,14-Trimethylpentadecane-2-on (8.36%), tributyl 2-acetylcitrate (5.46%), b-caryophylline (5.44%), cyclodeka-1.5-diene (3.24%) ), (-) - b-cubeben (2.58%) and a-bisabolen (2.46%) were described in experimental data.